Characterization and quantitation of polyphenolic compounds in Senna gardneri and S. georgica from the Northeast of Brazil - Maia, Irvila Ricarte de O.; Trevisan, Maria T.S.; Silva, Maria Goretti de V.; Breuer, Andrea; Owen, Robert (Natural product communications, 2018)
Because there is a dearth of data on the taxon Senna, the aim of this study was to determine the phytochemical composition of various botanical parts of Senna gardneri Irwin & Barneby and Senna georgica Irwin & Barneby. A total of 24 polyphenolic compounds were identified in methanol extracts. The higher concentration (on a dry weight basis) of polyphenolic compounds, was detected in the leaves (29.3 g/kg) and roots (17.3 g/kg) of S. gardneri. By contrast, a lower concentration of polyphenolic compounds were detected in the roots of S. georgica (11.8 g/kg), followed by the bark (5.8 g/kg), leaves (0.7 g/kg) and fruits (0.3 g/kg). Flavonoids comprised the major polyphenolic compounds in leaves of S. gardneri (98 %) and S. georgica (100 %) and the bark of S. georgica (86 %). Whereas the composition was quite different in the roots, of which the major components were stilbenes and naphthapyrones at 87 % and 13 % in S. georgica roots and 64 % and 28 % in S. gardneri roots. The fruits of S. georgica contained only one anthraquinone. In conclusion the roots of S. gardneri (11.023 g/kg) and S. georgica (10.285 g/kg) are a rich source of stilbenes, which have promising cancer chemopreventive capacities.